Analisis Keterlambatan Pemuatan Clinker Terhadap Efisiensi Operasional di Pelabuhan Khusus PT. Semen Indonesia - Mochammad Rahman Irzam Ar-Rafi; Sutini (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2025)
This study aims to analyze the impact of clinker loading delays on operational efficiency on MV. Qi Fu and MV. Queen Aliyah at PT. Varia Usaha Bahari, Tuban branch. Delays in clinker loading that occur on both ships can cause ships to be late in loading activities, thereby reducing the operational productivity of the Port. The research method uses quantitative with an approach through observation, document analysis, and documentation studies. The reference used in this study uses descriptive statistical analysis calculations which include three variables, namely bad weather, equipment damage, and truck queues. The results of the analysis show that MV. Qi Fu has a significant level of delay, which is 87.16%, compared to MV. Queen Aliyah which only reached 59.60%. This difference shows that the inhibiting variables have a major impact on loading performance, especially on weather conditions and equipment damage. This study provides recommendations to overcome delays so as to optimize the clinker loading process, equipment damage variables through periodic maintenance, weather through real-time monitoring, and truck queues through optimization by improving coordination between related parties.